Pengaruh Penambahan Tepung Kacang Merah dan Tepung Ubi Jalar Ungu (Ipomoea batatas var Ayumurasaki) terhadap Sifat Fisik, Sensoris serta Kimia Chewy Cookies - Oktavianisa Rakhmayati; Khusnul Khotimah; Rizka Mulyani; Indrati Kusumaningrum (Journal of Applied Agriculture, Health, and Technology, 2023)
Cookies are a dry cake with a crunchy texture and refined grains. Cookies are usually made from the main ingredient, flour and other additives, sugar, eggs, and fat such as butter or margarine. Wheat flour contains a lot of gluten which, if consumed too much, will damage the lining of the small intestine, prevent the absorption of food nutrients, and cause diarrhea, anemia, osteoporosis, infertility, and several other diseases. The substitution of purple sweet potato flour high in anthocyanin and red bean flour high in fiber is one of the efforts to produce good quality chewy cookies which are beneficial for health. This study aim to determine the composition of the addition of red bean flour and purple sweet potato flour to chewy cookies in terms of physical, sensory, and chemical properties. This study used a completely randomized design with 1 factor, namely the ratio of wheat flour: kidney bean flour: purple sweet potato flour A1 (50% : 30% : 20%), A2 (50%: 25%: 25%) and A3 (50% : 20% : 30%) with a total of 300 g. The results show that overall the most preferred chewy cookies are A2 which includes color, aroma, taste and texture. While the chemical composition showed moisture content, ash content, protein, crude fiber, fat, and carbohydrates respectively 6.94%, 0.98%, 5.44%, 2.38%, 24.85%, 59.94%.